The Representation of Communicative Competence in the Arabic Language Learning Outcomes of Indonesia's Merdeka Curriculum - Sholahudin, Shofwan; Idris, Ilham Maulana Ali; Abdurahman, Maman (Study Program of Arabic Language Teaching, 2025)
This study aims to analyse the representation of communicative competence in the Arabic Language Learning Outcomes (LO) of the Merdeka Curriculum. The research seeks to ensure a balance between linguistic accuracy and contextual communication skills in the national curriculum. Using a qualitative approach with a directed content analysis, the study adopts the frameworks of Canale and Swain (1980) and Canale (1983), which encompass grammatical, sociolinguistic, discourse, and strategic competences. The corpus comprises the official Arabic Language Law issued through the Decree of the Director General of Islamic Education No. 3302 of 2024. The analysis employed Mayring's (2000) six-step deductive category application, covering the definition of focus, formulation of analytical aspects, category development and revision, full coding with reliability checks, and interpretation of meaning patterns. The findings show that the LO presents a progressive yet uneven development of communicative competence. Grammatical and discourse competences are explicitly structured and systematically developed across all learning phases (A–F), while sociolinguistic and strategic competences remain implicit and underrepresented. In conclusion, the LO still prioritises linguistic accuracy and textual cohesion over adaptive and pragmatic skills required for authentic communication. The study emphasizes the importance of explicitly integrating sociolinguistic and strategic dimensions into curriculum design and teaching practices to enhance learners' ability to communicate effectively, contextually, and meaningfully.